Modified Xiaoyaosan (MXYS) Exerts Anti-depressive Effects by Rectifying the Brain Blood Oxygen Level-Dependent fMRI Signals and Improving Hippocampal Neurogenesis in Mice - Gao, Lei; Huang, Peng; Dong, Zhaoyang; Gao, Tingting; Huang, Shaohui; Zhou, Chuying; Lai, Yuling; Deng, Guanghui; Liu, Bin; Wen, Ge; Lv, Zhiping (Frontiers in Pharmacology, 2018)
As the traditional Chinese herbal formula, Xiaoyaosan and its modified formula have been described in many previous studies with definite anti-depressive effects, but its underlying mechanism remains mystery. Previous work in our lab has demonstrated that depression induced by chronic stress could generate brain Blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) signals disorder, accompanied by the impairment of hippocampal neuronal plasticity, decrease of brain-derived neurotrophic factor (BDNF), and reduction of the number and complexity of adult neurons in the dentate gyrus. We hypothesized that herbal formula based on Xiaoyaosan could exert anti-depressive effects through restoring these neurobiological dysfunctions and rectifying BOLD-fMRI signals. To test this hypothesis, we examined the effect of modified Xiaoyaosan (MXYS) on depressive-like behaviors, as well as hippocampal neurogenesis and BOLD signals in a mice model of CUMS-induced depression. MXYS exerted anti-depressant effects on CUMS-induced depression that were similar to the effects of classical antidepressants drug (Fluoxetine hydrochloride), with a significant alleviation of depressive-like behaviors, an improvement of hippocampal neurogenesis, and a reversal of activation of BOLD in the limbic system, particularly in the hippocampus. These results suggested that MXYS attenuated CUMS-induced depressive behaviors by rectifying the BOLD signals in the mice hippocampus. These novel results demonstrated that MXYS had anti-depressive effects accompanied by improving BOLD signals and hippocampal neurogenesis, which suggested that BOLD-fMRI signals in brain regions could be a key component for the evaluation of novel antidepressant drugs.